Advancing Knowledge: IJSIRT's Latest Research Insights - Pradhan, Bijay Lal (International Journal of Silkroad Institute of Research and Training, 2024)
<div class="min-h-[20px] text-message flex w-full flex-col items-end gap-2 whitespace-pre-wrap break-words [.text-message+&]:mt-5 overflow-x-auto" dir="auto" data-message-author-role="assistant" data-message-id="f4700fb7-cacd-4db9-8ff4-76d8e1fbb9dd"> The second volume of the International Journal of Silkroad Institute of Research and Training (IJSIRT) continues to explore and share new knowledge. The first volume covered diverse research topics, including public health, economic policies, and healthcare practices. IJSIRT aims to support researchers by providing a platform for sharing findings and fostering interdisciplinary conversations. The current volume focuses on Biomedical Science. The journal encourages engagement and submissions from researchers to build a vibrant, inclusive community that drives innovation and addresses complex global challenges. 4o